Identification of high-risk patients for development of type B aortic dissection based on novel morphological parameters - Li, Da; Wang, Jiarong; Zhao, Jichun; Wang, Tiehao; Zeng, Xiangguo; Zheng, Tinghui; Yuan, Ding (Frontiers in Physiology, 2023)
Background: Predicting development of sporadic type B aortic dissection (TBAD) always remains a difficult issue. This study aimed to identify high-risk patients for development of TBAD based on morphological parameters. Methods: This propensity-score matched case-control study collected and reconstructed the computed tomography angiography of acute TBAD patients and hospital-based control participants without aortic dissection from January 2013 to December 2016. Multivariate regression analysis was used to calculate adjusted odds ratio (aOR) and 95% confidence interval (CI). Discriminant and reclassification abilities were compared between our model with a previously established model. Results: Our study included 76 acute TBAD patients and 79 control patients (48 cases and 48 controls after propensity-score matching). The degree of question mark (aOR 1.07, 95%CI 1.04-1.11), brachiocephalic trunk diameter (aOR 1.49, 95%CI 1.20-1.85), brachiocephalic trunk angle (aOR 0.97, 95%CI 0.94-0.99), aortic root diameter (aOR 1.31, 95%CI 1.15-1.48), and aortic width (aOR 1.12, 95%CI 1.07-1.17) were associated with a significantly increased risk of TBAD formation. Similar findings were observed in the propensity-score matching and sensitivity analysis only including hyperacute TBAD patients. A novel prediction model was established based on the above parameters. The new model showed significantly improved discriminant ability compared with the previously established model (c-index 0.78 [95%CI 0.71-0.85] vs. 0.67 [95%CI 0.58-0.75], P=.03), driven by increased reclassification ability in identifying TBAD patients (NRI for events 0.16, 95%CI 0.02-0.30, P=.02). Conclusion: Morphological predictors, including the degree of question mark, aortic width, aortic root diameter, brachiocephalic trunk angle, brachiocephalic trunk diameter, may be used to identify patients at high risk of TBAD.